The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/buildings9010022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Building Microclimate on the Thermal Environment of Traditional Japanese Houses during Hot-Humid Summer

Abstract: The purpose of this study was to investigate the effects of building microclimate on the indoor thermal environment of traditional Japanese houses, focusing especially on the shading effect of trees as well as the cooling effect of spraying water. Basically, the indoor thermal environment was found to follow the outdoor conditions due to the open-plan and lightweight wooden structure. Nevertheless, air temperatures of the living rooms in the two case study houses were lower than the corresponding outdoors by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As originally constructed, houses in relatively warm areas in Japan, including Kyo-machiya, provide a high natural air change rate and were designed to reduce indoor temperatures during summer. Hosham et al clarified that indoor temperature can be 2 ℃ lower than the corresponding outdoor temperature in summer [3]. However, their extensive air leakage owing to their unique structure, as well as their poor thermal insulation resulting from their traditional appearance and materials, can lead to discomfort and high heating energy consumption during winter [4], as shown in a study conducted by Ooka in the Hokuriku district, confirming cold and discomfort in winter [5].…”
Section: Research Backgroundmentioning
confidence: 99%
“…As originally constructed, houses in relatively warm areas in Japan, including Kyo-machiya, provide a high natural air change rate and were designed to reduce indoor temperatures during summer. Hosham et al clarified that indoor temperature can be 2 ℃ lower than the corresponding outdoor temperature in summer [3]. However, their extensive air leakage owing to their unique structure, as well as their poor thermal insulation resulting from their traditional appearance and materials, can lead to discomfort and high heating energy consumption during winter [4], as shown in a study conducted by Ooka in the Hokuriku district, confirming cold and discomfort in winter [5].…”
Section: Research Backgroundmentioning
confidence: 99%
“…This measure also showed that designing for adaptation is vital, and that there are different ways of designing for climate adaptability. For instance, some measures were presented as climate-adaptive/climate-responsive designs [3,46,47], some as architectural designs that can be applied to rural residences [48], some as building microclimate designs [49], traditional dwelling designs [50][51][52][53], roof designs [54,55], design criteria or regulations [56][57][58], passive house designs [19,[59][60][61], building envelope designs [62][63][64], adaptation designs for social housing [65], and some as structural designs [66][67][68]. Skins for buildings capable of responding to external and internal conditions and implementing context-aware functions.…”
Section: Climate-adaptive Measures Related To Housing and Its Categor...mentioning
confidence: 99%
“…Additionally, designing for climate adaptation not only covers the indoor environment or the building per se, but it may be applicable to outdoor environments as well. As illustrated by Hosham and Kubota [49], the design of the microclimate also affects indoor conditions (e.g., temperature and shading). This could be improved by the incorporation of natural shading sources, such as trees and vegetation or water spraying.…”
Section: Risk Profiling [T5]mentioning
confidence: 99%
“…Office buildings (including 23% of nonresidential buildings) are responsible for more than 48% of the annual energy demand (heating and cooling) in urban areas [5,6]. It is commonly accepted that urban 2 of 19 microclimate conditions have a significant impact on urban climates [7,8], urban comfort [9,10], and the energy performance of buildings [11,12]. At the urban microscale level, the average wind speed is lower, with more complex flow patterns as compared to rural areas [13].…”
Section: Introductionmentioning
confidence: 99%